Efek Samping Terapi Antiretroviral dan Kepatuhan Berobat Penderita HIV/AIDS - Sitorus, Rico Januar; Novrikasari, Novrikasari; Syakurah, Rizma Adliah; Natalia, Merry (Jurnal Kesehatan, 2021)
Antiretroviral treatment side-effects and patient compliance with medical instructions continue to be a growing challenge for HIV/AIDS patients. Arv therapy has resulted in a substantial intervention that has been successful in preventing transmission and opportunistic infection. The main objective of this study was to analyze the association between side-effects of ARV therapy and medication adherence as well as another potential confounding such as opportunistic infection, family support, stress level, knowledge of ARV, marital status, and occupation. This study is a quantitative approach by using cross-sectional methods. A total of 244 respondents from 1.180 patients with confirmed HIV registered in the Care Support and Treatment (CST) service and Sriwijaya Community in the City of Palembang to respond to the survey. Non-random sampling was used to collect the samples. As the result, the majority of the respondents were male (84,43 %), â‰¥30 years old (57,4%), and secondary school graduates (52%). After adjusting with stress and opportunistic infection variable, a Multivariate regression analysis revealed a positive relationship between side effects and medication adherence (p-value of 0,041; 0,05), OR Adj 2,131 (1,190-4,988). PLHV who had adverse effects had a 2.131 times worse adherence rate than those who did not. In conclusion, medication adherence must be greatly improved in light of therapeutic side effects, stress levels, and opportunistic infection.